IJV Phlebectasia: an approach algorithm - Rao, Karthik N.; Chavan, Shrinivas S.; Kale, Vitthal D.; Hekare, Amol; Sylendran, Archana; Khond, Abishek (International Surgery Journal, 2017)
Internal jugular venous (IJV) Phlebectasia are rare disorders. It is generally diagnosed at an early age, usually unidentified or misdiagnosed or ignored because of the scarcity of the knowledge on the disorder. We encountered a case of 7-year-old child with a right sided intermittent neck swelling which mimicked as an external laryngocele. But, the diagnosis of IJV Phlebectasia was made on “dynamic” ultrasound (USG) doppler study. Cervical adenopathy, mediastinal masses, tuberculosis and certain syndromes of connective tissue disorders were ruled out. The child was managed conservatively with parents and the child being educated about disorder.